Emotional intelligence and styles of affront to stress in university students of education - Añorga-Zavaleta, Rosmery (2020)
The investigation aimed to determine the relationship between emotional intelligence and coping styles in a sample of 198 students. The research was embodied under the quantitative approach of the basic type. The non-experimental cross-sectional design was selected. In the first place, the instruments were validated; secondly, the reliability of the instruments; thirdly, the survey was applied to the analysis units in 30-minute sessions in person; fourth, the data was tabulated and descriptive and inferetial statistics were carried out. It was concluded that there is a positive, significant and very high relationship between both variables given that the degree of relationship of the variable emotional intelligence and coping styles to stress was rs = 0.912, in addition, it was found that its significance was less than 5% (p = 0.00).